Pengaruh Komunikasi, Kerjasama Tim, Kreativitas Terhadap Kinerja Pegawai Negeri Sipil Pada Badan Pendapatan Daerah (Bapenda) Kabupaten Paser - Harmayanto Harmayanto; Nuriyah Nuriyah; Ahmad Faisal (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The purpose of this research is to determine the influence of communication, teamwork, creativity on the performance of civil servants at the Paser Regency Regional Revenue Agency (BAPENDA). From the results of the validity test of 18 valid statements and the significant limit of rtable is 0.05 and the two-sided test, the rtable value is 0.2876 while rcount > rtable for each statement in this study. The results of the reliability test, the Cronbach Alpha value is 0.903, the N of items is 18. From the results of data analysis and data tabulation, it can be seen that the results of the regression equation are Y= 0.477+0.404 X1+0.245 X2+0.242X3. Based on the calculation results, the R value (correlation coefficient) of 0.842 is at a relationship level of 0.80-1.000, which means it is at a very strong relationship level between the variables communication (X1), teamwork (X2), and creativity (X3) on performance. employee (Y). The Adjusted R Square value (coefficient of determination) is 0.688 or 68.8%. This shows that the variables communication (X1), teamwork (X2), and creativity (X3) contribute or contribute an influence of 68.8% to the performance of civil servants (Y) at the Paser Regency Regional Revenue Agency (BAPENDA). Meanwhile, the remaining 31.2% was influenced by other variables not included in this research. The Fcount test results obtained a value of 34.796 with a significance level of 0.000 while the Ftable value was 2.82 (3:43). So Fcount is 34.796 > Ftable value is 2.82. This means that there is a joint influence between the variables communication (X1), teamwork (X2), and creativity (X3) on employee performance (Y). The results of the t test obtained a Communication tcount (X1) value of tcount 3.094 > ttable 2.017 with a significance level of 0.003 < 0.05. So H0 is rejected and Ha is accepted. Teamwork (X2) tcount is 2.454 > ttable is 2.017 with a significance level of 0.018 < 0.05. So H0 is rejected and Ha is accepted. Creativity (X3) tcount is 1.983 < ttable is 2.017 with a significance level of 0.054 > 0.05. So H0 is accepted and Ha is rejected.